Practical Ext JS 4 - Sunderaraman, Prabhu. (Apress : Imprint: Apress, 2013)
Practical Ext JS 4 will get you up and running, using Ext JS 4.2 for your projects, as quickly as possible. After a quick refresher on some JavaScript basics, you will get to grips with Ext JS 4s OO concepts (such as mixins) and familiarize yourself with its UI components and layout. You'll learn all the core features of the Ext JS framework, such as its MVC architecture, theming and styling your applications, and displaying data through components such as grids, trees, and charts. You'll use the Ext JS components and create an entire application from scratch by following the many practical examples. Finally, you'll learn about unit testing and packaging to build and deploy better applications. Provides you with a solid knowledge of the building blocks of Ext JS 4 Takes you through developing applications using the MVC architecture Demonstrates extending the UI with custom components and plugins Shows you how to unit test Ext JS 4 applications with Jasmine and deploy them with Sencha Cmd Completely up-to-date for the latest Ext JS 4.2